THE ROLE OF SUSTAINABLE HUMAN RESOURCE MANAGEMENT IN ACHIEVING ORGANIZATIONAL SUSTAINABILITY - Misrokiah Husni Batubara; Kiki Aulia Paramita; Himi Agustina Daulay; Fauziah Nur Lubis; Sri Afrida Wahyuni; Rakesh Sitepu; Anggia Sari Lubis (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
The global awareness of sustainability encompassing economic, social, and environmental aspects has fundamentally shifted corporate paradigms. Organizational sustainability is no longer seen as achievable through business strategy and technology alone but is critically dependent on how human resources are managed. This study aims to analyze the role of Sustainable Human Resource Management (Sustainable HRM) in realizing organizational sustainability. Using a descriptive analysis method, this research synthesizes and examines the theoretical foundations and practical applications of Sustainable HRM. The results indicate that Sustainable HRM, which integrates the principles of the Triple Bottom Line into HR practices, acts as a key facilitator for a sustainability culture, develops sustainable leadership, and aligns employee values with long-term organizational goals. Key practices distinguishing it from conventional HRM include Green HRM initiatives, promoting employee well-being and diversity, and fostering competency development for long-term employability. However, implementation faces challenges such as a lack of top management awareness and resistance to change. Conversely, it offers significant opportunities, including enhanced corporate reputation, increased employee engagement, and long-term resilience. The study concludes that Sustainable HRM is a strategic imperative for organizations seeking comprehensive and enduring sustainability.